Analisis Kontroversi Childfree di Media Sosial dalam Relasinya dengan Feminisme dan Budaya Ketimuran - Nur Afifah Afif; Zainul Ahwan (Universitas Merdeka Malang, 2024)
This research aims to reveal how the childfree controversy on social media relates to feminism and eastern culture using a review. This research is descriptive qualitative with a virtual research approach using units of analysis in the form of text, images, comments from netizens, as well as news about the childfree controversy which started on social media Instagram, TikTok and YouTube. The results of the analysis of Sara Mills' critical discourse show that the position of netizens is as a subject who provides criticism or support, while the position of actors is as an object in discourse construction. The childfree controversy also has implications for views of feminism and eastern culture, as the finding that childfree views from actors triggers pro and con responses from netizens.